Effect of the use of deslorelin acetate in the induction of ovulation of Peruvian Paso mares - Chávez C., Elsa (2018)
The study was conducted in 16 cyclic mares of the Peruvian Paso breed from the province of Ascope, La Libertad, Peru, between January and March 2017, to evaluate the effect of deslorelin acetate administration on ovulation time and pregnancy rate. There was a control group (n=8) without treatment and an experimental group (n=8) treated with 1.75 mg of deslorelin acetate when observing a dominant follicle of 38-40 mm and a grade 2 to 3 of edema endometrial determined by ultrasound. The mares were inseminated at 16-24 h afterwards. The ultrasound monitoring was continued until ovulation and pregnancy diagnosis was done 13-15 days after ovulation. The ovulation time was 43.13 ± 4.48 and 69.00 ± 8.41 h for the experimental and control group, respectively. Ovulation within 48 h occurred in 87.5% (7/8) of the mares in the treated group, while only in 37.5% (3/8) of the control group did. The pregnancy rate was 87% (7/8) in the treated group and 50% (4/8) in the control group; in all cases without finding significant statistical differences.